2015
DOI: 10.5433/1679-0359.2015v36n3supl1p2175
|View full text |Cite
|
Sign up to set email alerts
|

Consumo e comportamento ingestivo de cabras em pasto de capim-marandu

Abstract: ResumoO experimento foi conduzido para avaliar a influência da altura do pasto (30, 40, 50 e 60 cm) de capimMarandu (Brachiaria brizantha) sobre características estruturais do dossel, comportamento em pastejo e processo de ingestão de forragem por caprinos. Para a avaliação do comportamento em pastejo foram utilizadas seis cabras e, do processo de ingestão, quatro cabras, todas da raça Anglonubiana. Adotou-se o delineamento inteiramente casualizado, com duas repetições no espaço e duas repetições no tempo. O a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Conversely, pastures managed at 45 cm pregrazing canopy height had a higher proportion of senescent material and stem mass due to its greater elongation. Likewise, Macedo et al (2015) found a higher proportion of senescent material with increasing canopy heights in Marandu grass, and they associated it with the higher self-shading and stem elongation that intensifies the senescence process of older leaves. As can be observed in Table 3, TDM yield has a negative correlation with the proportion of leaf blades (r = -0.95) but positive with those of stem (r = 0.96) and senescent material (r = 0.95).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Conversely, pastures managed at 45 cm pregrazing canopy height had a higher proportion of senescent material and stem mass due to its greater elongation. Likewise, Macedo et al (2015) found a higher proportion of senescent material with increasing canopy heights in Marandu grass, and they associated it with the higher self-shading and stem elongation that intensifies the senescence process of older leaves. As can be observed in Table 3, TDM yield has a negative correlation with the proportion of leaf blades (r = -0.95) but positive with those of stem (r = 0.96) and senescent material (r = 0.95).…”
Section: Resultsmentioning
confidence: 88%
“…Thus, proper canopy height management is essential to increase FA, without significant losses in quality due to increased stem production. Brâncio et al (2003) found a correlation of r = 0.70 between canopy height and FA in Massai grass, whereas Macedo et al (2015) found a correlation of r = 0.91 for the same factors in Marandu grass.…”
Section: Resultsmentioning
confidence: 97%
“…Animals change the parameters of their ingestive process in an attempt to meet their intake requirements, because variables such as bite mass and forage-intake rate differ according to pasture structure, especially height. Changes in pasture height might affect the time required to grasp and chew the food, which consequently alters intake of forage (MACEDO et al, 2015).…”
Section: Introductionmentioning
confidence: 99%